1996
DOI: 10.1136/gut.39.4.551
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal transit in anxiety and depression.

Abstract: (14 (6-29) hours) than in patients with depression (49 (35-71) hours) (p<0.001), and controls (42 (10-68) hours) (p<0-001). In patients with anxiety, orocaecal transit time was shorter (60 (10-70) minutes) than in patients with depression (110 (60-180) minutes) (p<0.01), and shorter than in controls (75 (50-140)) minutes (p<0.05). The prolongation oftransit times in depression compared with controls was not significant. However, WGTT correlated with both the Beck Depression Inventory score (r=0.59, p<0.01) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 38 publications
8
57
0
3
Order By: Relevance
“…These findings are entirely consistent with the view that people who experience greater symptoms of constipation experience both higher levels of depression and impact upon their QoL. Previous research 210 indicates that anxiety is linked to increased gut transit time. Our results are at odds with this finding as our anxiety scores were also positively correlated with constipation symptoms.…”
Section: Pac-sym Pac-qol and Anxiety/depressionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are entirely consistent with the view that people who experience greater symptoms of constipation experience both higher levels of depression and impact upon their QoL. Previous research 210 indicates that anxiety is linked to increased gut transit time. Our results are at odds with this finding as our anxiety scores were also positively correlated with constipation symptoms.…”
Section: Pac-sym Pac-qol and Anxiety/depressionsupporting
confidence: 90%
“…210 On the HADS, each item is marked on a four-point (0-3) response category. Scores can range from 0 to 21 for anxiety and 0 to 21 for depression.…”
Section: Pac-sym Pac-qol and Anxiety/depressionmentioning
confidence: 99%
“…MDT-stress significantly increased the pulse rate and respiratory rate in this study. It is reported that anxiety is associated with increased bowel frequency, while depressed patients tend to be constipated (Gorard et al, 1996). It is also reported that anxiety correlated negatively with rectal mucosal blood flow (Emmanuel et al, 2001).…”
Section: Correlation Of Both Anxiety and Depression Scores And The Lfmentioning
confidence: 94%
“…Accordingly, even the topographic EGG maps based on absolute power itself and the absolute power ratios demonstrated gastric inhibition and colonic facilitation during MDT and postprandial epigastric facilitation. Approximate power ratios are indicated by symbol (<) and numerical figures, such as<1.0, 2.0, or <5, 8, 10, 20, and 30. stress significantly increased the bowel frequency, while depressed patients tended to be constipated (Gorard et al, 1996).…”
Section: Colonic Activitymentioning
confidence: 99%